Analisis Peran Harga, Variasi Produk Dan Kualitas Produk Terhadap Customer Satisfaction Produk Konveksi - Abdurrahim Abdurrahim; Hendy Tannady; Dhiana Ekowati; Winanto Nawarcono; Arief Budi Pratomo (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to find out how much in attracting consumers to buy the products offered, it is necessary to have high quality product quality, competitive price perceptions, and diverse product variations, so as to provide satisfaction to consumers. This research is a quantitative approach using the SPSS Static 25 program with a sample of 100 respondents who live in Jabodetabek who have purchased Bunda Collection clothing using non- probability sampling and purposive techniques. The results of this study t test shows that product quality has an effect on customer satisfaction with a significance value of 0.000 < 0.5 and a t value of 10.923 > 1.984 so that product quality is very important Mother Collection, price variable 4.075 > 1.984 has an effect and product variation variable 118.004 > 1.984 has a significant effect . The benefit of this research for Bunda Collection is as input or evaluation material in order to maintain and improve product quality, price, and product variations in order to excel from other competitors.